Family Support and Exclusive Breastfeeding (INCH : Journal of Infant and Child Healthcare, 2023)
Family support can increase the mother's confidence and encourage her to choose exclusive breastfeeding for babies up to 6 months. This study aimed to determine the relationship between family support and exclusive breastfeeding. This research is a descriptive study with a cross-sectional design. The sample was 52 mothers who had babies aged 6-12 months. The sampling technique was random sampling. Data analysis used the chi-square test. This study found a significant relationship between family support and exclusive breastfeeding with Fisher's exact values (p-value = 0.032). Family support in the "favorable" category at 76.67% and the "unfavorable" category at 13.33%. Exclusive breastfeeding in the "yes" category was 28.33%, and "no" was 71.67%. Respondents with good family support but did not give exclusive breastfeeding to their babies at 51.9%, and respondents with low-income family support did not provide exclusive breastfeeding at 15.4%